Integrative Functional, Molecular, and Transcriptomic Analyses of Altered Intrinsic Timescale Gradient in Depression - Han, Shaoqiang; Zheng, Ruiping; Li, Shuying; Zhou, Bingqian; Jiang, Yu; Wang, Caihong; Wei, Yarui; Pang, Jianyue; Li, Hengfen; Zhang, Yong; Chen, Yuan; Cheng, Jingliang (Frontiers in Neuroscience, 2022)
The pathophysiology and pharmacology of depression are hypothesized to be related to imbalance of excitation-inhibition that gives rise to hierarchical dynamics (or intrinsic timescale gradient) further supporting a hierarchy of cortical functions. On this assumption, intrinsic timescale gradient is theoretically altered in depression. However, it remains unknown. We investigated altered intrinsic timescale gradient recently developed to measure hierarchical brain dynamics gradient and its underlying molecular architecture and brain-wide gene expression in depression. We first presented replicable intrinsic timescale gradient in two independent Chinese Han datasets then investigated altered intrinsic timescale gradient and its possible underlying molecular and transcriptional bases in patients with depression. As a result, patients with depression showed stage-specifically shorter timescales compared with healthy controls according to illness duration. The shorter timescales were spatially correlated with monoamine receptors/transporters densities suggesting the underlying molecular basis of timescales aberrance and providing clues to treatment. In addition, we identified that timescales aberrance related genes ontologically enriched for synapse-related and neurotransmitter (receptor) terms elaborating the underlying transcriptional basis of timescales aberrance. These findings revealed atypical timescale gradient in depression and built linking between neuroimaging, transcriptome and neurotransmitter information facilitating an integrative understanding of depression.